An Exploratory Study Of The Experiences Of Young Women And Men As Members Of Pakatan Rakyat: A Case Study In Penang, Kuala Lumpur And Selangor, Malaysia - Teo, Sue Ann (2010)

(untitled)
This study explores and analyzes the differences in the experiences of young male female members of Pakatan Rakyat component parties in Penang, Kuala Lumpur Selangor. Members of these parties within the coalition of PR were chosen as responden s because of the recent introduction of a new party structure that consolidates young worn and men in the same youth wing which has given rise to an opportunity to document a study their experiences. This study attempts to identify facilitating factors and constrain influencing their experiences in the parties. Kajian ini meneroka dan menganalisis pengalaman yang berbeza antara pemuda pemudi sebagai ahli parti politik Pakatan Rakyat di Pulau Pinang, Kuala Lumpur Selangor. Kajian terhadap ahli-ahli parti-parti ini dibuat kerana PKR dan D memperkenalkan struktur baru, iaitu menggabungkan pemuda-pemudi di bawah sayap ya g sama, sementara PAS mengekalkan struktur asal partinya, iaitu memisahkan pemuda pemudi PAS kepada dua sayap yang berasingan.